Pemenuhan Hak Anak Setelah Lahir Melalui Tahnik dan Aqiqah: Kajian Fiqh dan Pendidikan Islam - Erliyana, Erliyana; Prasetyo, Nabil Tito; Kholid, Idham; Ghazi, Fachrul; Erlina, Erlina (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study explores tahnik and aqiqah as expressions of fulfilling children's rights within the framework of Islamic jurisprudence (fiqh) and Islamic education. Both are classified as sunnah muakkadah practices that hold not only ritual significance but also deep spiritual, social, and pedagogical values. The aim is to analyze how these practices function as early educational media to instill monotheism, compassion, and moral responsibility from birth. This research employs a library-based approach with thematic analysis of classical and contemporary sources. Findings indicate that tahnik serves as the child’s first spiritual education, introducing faith and parental affection, while aqiqah embodies gratitude, social care, and character formation. The integration of fiqh and tarbiyah Islamiyah highlights that fulfilling children’s rights in Islam begins at birth through spiritually and educationally meaningful practices. The study underscores the importance of revitalizing the meaning of tahnik and aqiqah beyond tradition, as integral instruments for nurturing morality and spirituality in Muslim families.